The World Health Organization (WHO) approach to healthy ageing. (September 2020) - Rudnicka, Ewa; Napierała, Paulina; Podfigurna, Agnieszka; Męczekalski, Błażej; Smolarczyk, Roman; Grymowicz, Monika
Highlights: The ageing global population is the important medical and social demographic problem. WHO underlines the importance of maintaining functional ability in older age. WHO identified strategic objectives and priorities to promote healthy ageing. Person-oriented long-term integrated care is the key issue. Abstract: The ageing of the global population is the most important medical and social demographic problem worldwide. The World Health Organization (WHO) has defined healthy ageing as a process of maintaining functional ability to enable wellbeing in older age. The WHO, Member States and Partners for Sustainable Development Goals have created a Global Strategy and Action Plan for Ageing and Health for 2016–2020 and its continuation with the WHO programme The Decade of Healthy Ageing 2020–2030. The WHO has established main priorities such as supporting country planning and action, collecting better global data and promoting research on healthy ageing, aligning health systems to the needs of older people, laying the foundations and ensuring the human resources necessary for long-term integrated care, undertaking a global campaign to combat ageism, and enhancing the global network for age-friendly cities and communities. There are several reports of coordinated preventive health and social health initiatives in well developed countries. However, there is little evidence on the application of the active ageing frameworks in developing countries. Greater national capacities and closer monitoring of the progress through age-disaggregated data is needed to effectively implement the intended programmes on healthy ageing.